Analysis of some renewable energy uses and demand side measures for hotels on small Mediterranean islands: A case study. (15th August 2018) - Beccali, M.; Finocchiaro, P.; Ippolito, M.G.; Leone, G.; Panno, D.; Zizzo, G.
Abstract: Tourist activity strongly influences the energy consumption and the overall load profile of communities with isolated energy systems. One example is hotel sectors on small islands that are not connected to mainland energy distribution grids. The use of solar energy systems could be a smart option for reducing energy consumption and tackling seasonal fluctuation. The operation of a weak and isolated electric grid requires attention to the management of power profiles in very short time frames. Energy storage (thermal or electric), as well as building automation control technologies, can be utilised for these aims. In this context, the present paper illustrates a study conducted at a hotel located on Lampedusa Island (Italy) that was considering some energy-retrofit scenarios dealing with the exploitation of renewable energy sources and building automation control technologies. The hotel is equipped with an air-to-water heat pump able to fulfil air conditioning and domestic hot water demands. Data concerning the hotel's energy consumption was measured during summer months while yearly data was provided by the local electric utility company. Detailed simulation models have been validated by this data and used to assess the efficacy of retrofit scenarios and their effects on the average daily electric profile. Highlights: A representative hotel on Lampedusa Island (ITALY) has been chosen. Simulations on actual hotel consumption are set up. Renewable Energy Source retrofit scenarios are proposed and evaluated by simulations. Solar options provide the most significant benefits.